Meaning and Reading in the Proverbs of El Conde Lucanor. - BAMFORD, HEATHER (Revista de Estudios Hispánicos, 2021)
We are adept readers of the fifty some exiemplos of Don Juan Manuel's fourteenth-century El Conde Lucanor; these exempla and the prologue that precedes them constitute a classic of medieval Spanish literature. This article analyzes the proverb books in this work, Books II-IV, to argue that the lack of studies on these sections amounts to a reading problem--or, more precisely, a failure to conceive of reading and the way meaning is produced and conveyed to readers in an appropriately ample sense. I begin with the familiar corteza y meollo hermeneutic to examine not what the proverbs mean but how they mean and through what processes they convey meaning. These processes include an uncovering, two-part hermeneutic: conveying meaning as though by accident or revelation; and through sonority, or by means of confusion via the combination of literal instances and metaphoric interpretation in which the metaphoric is the easier meaning to comprehend. Medieval readers may have read with a single goal, such as finding the author's intended meaning, engaging in the author's intended reading process, or locating what was most personally useful in that reading. However, a reader's purpose may instead have been dual, multiple, or undetermined; indeed, experiencing meaning in reading may have even meant going nowhere or failing to take away any content in particular.